Effects of stocking density on reared Siberian sturgeon (Acipenser baerii) larval growth, muscle development and fatty acids composition in a recirculating aquaculture system. (21st December 2018) - Aidos, Lucia; Vasconi, Mauro; Abbate, Francesco; Valente, Luisa M. P.; Lanfranchi, Marco; Di Giancamillo, Alessia
Abstract: This study evaluated the effects of rearing density on muscle growth and development in Siberian sturgeon ( Acipenser baerii ) larvae. Three different stocking densities were tested: low (LD, 30 larvae/l), mid (MD, 80 larvae/l) and high (HD, 150 larvae/l) in a recirculating aquaculture system. Larvae were sampled at hatching (T0), schooling (T1) and complete yolk‐sac absorption (T2) stage and were weighed and processed for muscle tissue histometrical analyses and for qualitative morphological study analyses; fatty acid profile was also determined by Gas Chromatography—Flame Ionization Detector analysis. Low‐density larvae presented a higher weight than MD or HD at T2 ( p < 0.05). Histometrical analysis revealed that total muscle area was similar at T1 and T2, but higher than T0, while it was lower at HD at schooling ( p < 0.05). The fatty acid profile revealed no differences between densities while, during development, there was a selective consumption: sparing or increasing of essential fatty acids to the detriment of their precursors. Our study suggests that lower densities appear to be more suitable to rear Siberian sturgeon in this particular stage of development. Indeed, larvae reared at the lower density were heavier and longer while larvae reared at the higher density showed lower muscle proliferation rate. As a consequence, LD larvae may exert an increase of potential growth at a mid‐long term.